The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2138/am-2017-5851
|View full text |Cite
|
Sign up to set email alerts
|

Representative size distributions of framboidal, euhedral, and sunflower pyrite from high-resolution X-ray tomography and scanning electron microscopy analyses

Abstract: A statistical procedure designed to obtain representative size distributions for different morphologies and arrangements of pyrite is described here. This statistical procedure is applied to data acquired during scanning electron microscopy (SEM) and high-resolution X-ray tomography (micro-CT) analyses. The statistical procedure was tested in methane-derived carbonate pipes recovered in the Gulf of Cadiz. These samples contain abundant pyrite together with pseudomorph iron oxyhydroxides showing multiple morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…This REV depends on the occurrence and size of the measured property. For MPy, previous works [12][13][14] have concluded that the REV is achieved when the number of objects is above 600-1000. The size and distribution of the MPy can be adjusted to a log-normal distribution, according to the Crystal Size Distribution (CSD) and the law of proportionate effect [28], which explains how a crystal population tends to grow in proportion to its size.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…This REV depends on the occurrence and size of the measured property. For MPy, previous works [12][13][14] have concluded that the REV is achieved when the number of objects is above 600-1000. The size and distribution of the MPy can be adjusted to a log-normal distribution, according to the Crystal Size Distribution (CSD) and the law of proportionate effect [28], which explains how a crystal population tends to grow in proportion to its size.…”
Section: Methodsmentioning
confidence: 96%
“…used to segregate the MPy subpopulations. More details about this process can be found in [11][12][13][14]. According to [27], an average sample volume scanned by MCT is much larger than the representative elementary volume (REV).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3d; cf. Merinero et al 2009Merinero et al , 2017Merinero and Cárdenes 2018). The diameter of this rare variety of framboids varies from 6 μm to 20 μm.…”
Section: Morphology and Size Distribution Of Pyrite Framboidsmentioning
confidence: 99%
“…The occurrence of small variety of pyrite framboids in the three intervals in well 570 indicates oxygendepleted depositional conditions (cf. Berner 1984;Wilkin et al 1996;Wei et al 2015;Merinero et al 2017;Rickard 2019). The abundance and size of framboids indicate their formation in the hydrogen sulfide-rich bottom water column.…”
Section: Morphology and Size Distribution Of Pyrite Framboidsmentioning
confidence: 99%